c-Fos expression in ouabain-treated vascular smooth muscle cells from rat aorta: evidence for an intracellular-sodium-mediated, calcium-independent mechanism - Taurin, Sebastien (Blackwell Science Inc, 2002)
In this study, we examined the effect of Na(+)–K(+) pump inhibition on the expression of early response genes in vascular smooth muscle cells (VSMC) as possible intermediates of the massive RNA synthesis and protection against apoptosis seen in ouabain-treated VSMC in our previous experiments. Incubation of VSMC with ouabain resulted in rapid induction of c-Fos protein expression with an approximately sixfold elevation after 2 h of incubation. c-Jun expression was increased by approximately fourfold after 12 h, whereas expression of activating transcription factor 2, cAMP/Ca(2+) response element binding protein (CREB)-1 and c-Myc was not altered. Markedly augmented c-Fos expression was also observed under Na(+)–K(+) pump inhibition in potassium-depleted medium. Na(+)–K(+) pump inhibition triggered c-Fos expression via elevation of the [Na(+)](i)/[K(+)](i) ratio. This conclusion follows from experiments showing the lack of effect of ouabain on c-Fos expression in high-potassium-low-sodium medium and from the comparison of dose responses of Na(+)–K(+) pump activity, [Na(+)](i) and [K(+)](i) content and c-Fos expression to ouabain. A fourfold increment of c-Fos mRNA was revealed 30 min following addition of ouabain to the incubation medium. At this time point, treatment with ouabain resulted in an approximately fourfold elevation of [Na(+)](i) but did not affect [K(+)](i). Augmented c-Fos expression was also observed under VSMC depolarization in high-potassium medium. Increments in both c-Fos expression and (45)Ca uptake in depolarized VSMC were abolished under inhibition of L-type Ca(2+) channels with 0.1 μM nicardipine. Ouabain did not affect the free [Ca(2+)](i) or the content of exchangeable [Ca(2+)](i). Ouabain-induced c-Fos expression was also insensitive to the presence of nicardipine and [Ca(2+)](o), as well as chelators of [Ca(2+)](o) (EGTA) and [Ca(2+)](i) (BAPTA). The effect of ouabain and serum on c-Fos expression was additive. In contrast to serum, however, ouabain failed to activate the Elk-1, serum response factor, CREB and activator protein-1 transcription factors identified within the c-Fos promoter. These results suggest that Na(+)–K(+) pump inhibition triggers c-Fos expression via [Na(+)](i)-sensitive [Ca(2+)](i)-independent transcription factor(s) distinct from factors interacting with known response elements of this gene promoter.